In Varietate Concordia: Two Perspectives on the European Values - Sazonova, Liliya Leonidovna (Conatus - Journal of Philosophy, 2019)
In the first chapter of the paper we elaborate on the attitude towards the Other in the European Union by discussing two adversative yet simultaneous processes taking place in the EU. The first tendency is a legacy from the centuries-lasting model of European unification against certain important Others. The second one refers to the aspiration of the supra-national European project to encourage in an unprecedented manner the co-existence with the otherness. We argue that this ambivalence results from the fact that the transformation of the attitude towards the otherness takes place with different tempo in the different social spheres. In the second chapter we develop further the reflection on the EU attitude towards the Other by focusing on the East European Other. We discuss the normative and de facto application of the European values both in the West and in the East part of the continent. In the last chapter we articulate two separate discourses framing the European values. The first one refers to the essentialist approach looking for a metaphysical reasoning of their universality by developing the common culture, history and spirit rhetoric. The second reading of the European values presents them in a more postmodern and debatable way and offers a mechanism for reconciling the heterogenic East-West European society.